Students' Perceptions of Using Grammarly Application in Enhancing Their Writing Ability - Ila Nurlia; Eliwarti; Supriusman (Acuity: Journal of English Language Pedagogy, Literature and Culture, 2025)
Grammarly application is one of the most widely used applications to assist students in enhancing their writing. This study aimed to find out students’ perceptions of using Grammarly application in enhancing their writing ability, and to explore specific areas of writing that can be enhanced by using Grammarly application. This study employed a mixed-method approach with a sequential explanatory design. The sample of this study was selected using purposive sampling technique. The quantitative data of this study was collected through questionnaire with 36 students of English study program at Universitas Riau. Meanwhile, the qualitative data was collected through a semi-structured interview with 7 students. The questionnaire results showed that students had positive perceptions towards Grammarly application as an application that is useful, easy to use, and effective in enhancing students’ writing. The interview results revealed that Grammarly helped students mostly in improving grammar, punctuation, capitalization, and spelling. In conclusion, Grammarly can be used as a supplementary tool to support the development of students’ writing ability.